A Pedagogical Approach Towards Ameliorating the Global Effects of Covid-19 Pandemic Through Forest Restoration and Environmental Sustainability - Olatoye, Tolulope Ayodeji; Fru, Raymond (Research in Social Sciences and Technology- OpenED Network, 2025)
This study investigated a pedagogical approach towards ameliorating the global effects of the COVID-19 pandemic through forest restoration and environmental sustainability. This research is considered apt and timely as it underscores the urgent need for forest restoration and environmental sustainability solutions in our fragile ecosystems amidst the ongoing COVID-19 pandemic and its associated challenges, such as forest degradation and the complexities of forest conservation. The study was conducted using a systematic review of the COVID-19 pandemic and its imminent challenges towards achieving forest restoration and environmental sustainability, drawing insights from renowned international academic journals, electronic publications, Google Scholar, and other academic websites. Pedagogically, integrating these findings into rural education curricula can significantly enhance students' understanding of environmental issues and the importance of sustainability. By incorporating concepts of forest conservation and environmental sustainability into classroom teachings, educators can foster a sense of environmental stewardship among students. Specifically, in rural education, equipping students with knowledge about sustainable practices and the challenges posed by the COVID-19 pandemic empowers them to engage in local conservation efforts and advocate for sustainable development within their communities. This approach not only prepares students to address environmental challenges but also promotes holistic development and improved quality of life in rural areas. Suggested strategies for curbing the adverse effects of COVID-19 include reforestation, preservation of wildlife habitats, and controlling human population growth and urbanization. This study provides recommendations on forest conservation and environmental sustainability to mitigate the impacts of the COVID-19 pandemic.